Impact of combinatorial immunotherapies in breast cancer: a systematic review and meta-analysis - Sisodiya, Sandeep; Kasherwal, Vishakha; Rani, Jyoti; Mishra, Neetu; Kumar, Sandeep; Khan, Asiya; Aftab, Mehreen; Shagufta,; Singh, Payal; Gupta, Ekta; Tanwar, Pranay; Hussain, Showket (Frontiers in Immunology, 2024)
Background: Breast cancer has the highest mortality rate among all cancers affecting females worldwide. Several new effective therapeutic strategies are being developed to minimize the number of breast cancer-related deaths and improve the quality of life of breast cancer patients.However, resistance to conventional therapies in breast cancer patients remains a challenge which could be due to several reasons, including changes in the tumor microenvironment.Attention is being divert towards minimising the resistance, toxicity, and improving the affordability of therapeutics for better breast cancer management. This includes personalized medicine, target-specific drug delivery systems, combinational therapies and artificial intelligent based screening and disease prediction. Nowadays, researchers and clinicians are also exploring the use of combinatorial immunotherapies among breast cancer patients, which have shown encouraging results for improved survival outcomes. This study attempts to analyse the role of combinational immunotherapies in breast cancer patients, and offer insights into their effective in breast cancer management.We conducted a systematic review and meta-analysis for which we selected the randomized clinical trials (RCTs) focused on completed Phase I/II/III/IV clinical trials investigating combination immunotherapies for breast cancer. The analysis aimed to assess the efficacy of combination therapies in comparison to mono therapies, focusing on overall survival (OS), and progression-free survival (PFS).We observed that, combination immunotherapies significantly (P<0.05) improved OS as compared to single-drug therapies in the Phase 1 with overall Risk ratio (RR) of 16.17 (CI 2.23,117.50) , Phase II with an overall Risk ratio (RR) of 19.19 (CI 11.76,31.30.00) and for phase III RR 22.27 (CI 13.600,36.37). In the case of PFS, it was also found significant with RR: 12.35 [CI 2.14, 71.26) in I phase RR 6.10 (CI 4.31, 8.64) in phase II, RR 8.95 (CI 6.09, 13.16) in phase III and RR 14.82 (CI 6.49, 33.82) in Phase IV of clinical trials.The observed improvements in overall survival and progression-free survival suggest that combination immunotherapies could serve as a better approach to breast cancer management.